Methods for analyzing environmental problems in the production and use of electricity (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The subject of this study is an analysis of the conditions under which environmental problems arise in the context of changes occurring in the energy sector and ways to use information and methodological approaches to address them. The aim of the study is to analyze the specifics of renewable energy use in the region and analyze ways to address environmental issues using statistical methods. The results will help identify solutions to environmental problems caused by energy sources produced and used in the region. The practical significance of the study’s results lies in solving environmental problems using methodological approaches, taking into account changes in the energy sector. The novelty of the study lies in the development of relevant provisions for addressing environmental issues in the industry and the possibility of their application in the energy sector. The results can be used to address environmental issues, taking into account changes in the energy sector, and taking into account the recommendations of relevant experts when implementing them in industry production.
Keywords: energy, renewable energy sources, climate, ecology, statistical method, energy con- servation, information support